Modelagem matemática e resolução de problemas de gerenciamento da produção utilizando programação linear - Zebediff, Nayara Bibiano (2015)
This study consists of a literature review about mathematical models of production management using linear programming, which aims to compare, from computational results, optimal solutions obtained and thus study them and analyze them. The study is methodologically characterized as a literature search, based on available previous researches. This work presents a background on linear programming, production management, mathematical modeling and a literature review on the topic. The simplex method is presented and applied as resolution method to obtain the optimal solutions. The results are obtained by running the models with computational support from the LINDO software. From the obtained optimal solutions, sensitivity analysis of the model parameters is implemented and the comparison of these solutions is made from computational point of view.